Basic Characteristics of a Magnetic Actuator for Capsule Endoscope - CHIBA, Atsushi; SENDOH, Masahiko; ISHIYAMA, Kazushi; ARAI, Ken Ichi (Transactions of Japanese Society for Medical and Biological Engineering, 2004)
In this paper, the authors propose applying a magnetic actuator to a capsule endoscope. We fabricated a capsule-type magnetic actuator and investigated its moving properties in a silicone tube and in pig intestines. The device consists of a dummy capsule measuring 11mm in diameter and 40mm in length, a magnetic actuator composed of a permanent magnet inside the dummy capsule and a 1-mmφ spiral structure outside the capsule. The permanent magnet is magnetized in the direction of the diameter. When a rotational magnetic field is applied, the magnetic actuator rotates and moves wirelessly. In this study, we measured the effect of the spiral shape on the velocity and thrust properties. According to our experimental results using the silicone tube, the optimal actuator was formed with 4 spirals set at a spiral angle of 45 degrees. In the subsequent moving test performed in pig intestines, the actuator traveled a distance of 450mm to its destination in the large intestine in 150s, and a distance of 400mm to its destination in the small intestine in 110s. This result confirms the potential applicability of the actuator as a guidance system for capsule endoscopes.